Evaluation of Oxidative Stress before and after Using Laser and Photoactivation Therapy as Adjuvant of Non-Surgical Periodontal Treatment in Patients with Rheumatoid Arthritis - Maria-Alexandra Martu; Petra Surlin; Luminita Lazar; George Alexandru Maftei; Ionut Luchian; Dorin-Nicolae Gheorghe; Elena Rezus; Vasilica Toma; Liliana-Georgeta Foia (MDPI AG, 2021)
(1) Background: The aim of this split-mouth design study was to analyze the clinical periodontal indexes and oxidative stress markers in gingival crevicular fluid modifications after three periodontal disease treatment possibilities (scaling and root planning-SRP; SRP and diode laser-L; SRP and photodynamic therapy-PDT). (2) Methods: The study was conducted on 52 patients: systemically healthy subjects with periodontal disease-non-RA (n = 26); and test group (n = 26) subjects with rheumatoid arthritis and periodontal disease-RA. Clinical periodontal measurements (probing depth-PD; Löe and Silness gingival index-GI; papillary bleeding index-PBI; and periodontal community index of treatment needs-CPITN) and oxidative stress markers (8-hydroxy-2'-deoxyguanosine (8-OHdG) and 4 hydroxynonenal (4-HNE)) were analyzed at baseline (T0), after three sessions of periodontal treatment (T1), and 6 months after treatment (T2). (3) Results: Periodontal therapy improved clinical periodontal measurements and oxidative stress markers in both analyzed groups, with supplementary benefits for laser- and PDT-treated periodontal pockets. (4) Conclusions: The analyzed oxidative stress markers decreased significantly following non-surgical periodontal therapy in both rheumatoid arthritis and systemically healthy patients. All the periodontal disease treatment possibilities analyzed in this study offered clinical and paraclinical improvements; however, the association of laser with SRP and photodisinfection with SRP yielded the best clinical and paraclinical outcomes when compared to SRP alone.